2018
DOI: 10.4038/jas.v13i1.8303
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Adoption of Maize Production Technologies: A study in Ghana

Abstract: Purpose: The huge gap between actual and achievable yields in Ghana’s maize production threatens Ghana’s household food security. Poor adoption of improved maize production technologies is often cited as the major cause of the low yields. This study examined the factors influencing adoption of improved production technologies by maize farmers in order to highlight the constraints and opportunities for improving adoption.Research Method: The data used were obtained through a cross-sectional survey of 576 maize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…The result relates with Asante-Addo et al 2017 andMustapha, Mohammed, andAbukari (2017), who noticed that, a farmer's purchasing power enables use of improved seeds hence positively impacting degree of market participation. The finding, however, contradicts studies by Ojo, Baiyegunhi, and Salami, (2019) and Wongnaa, Awunyo-Vitor, and Bakang (2018), who illustrated that inadequate access to farm credit impedes the adoption of improved technologies by farmers.…”
Section: Table 3: Factors Influencing Multiple Climate Change Adaptation Practicescontrasting
confidence: 72%
“…The result relates with Asante-Addo et al 2017 andMustapha, Mohammed, andAbukari (2017), who noticed that, a farmer's purchasing power enables use of improved seeds hence positively impacting degree of market participation. The finding, however, contradicts studies by Ojo, Baiyegunhi, and Salami, (2019) and Wongnaa, Awunyo-Vitor, and Bakang (2018), who illustrated that inadequate access to farm credit impedes the adoption of improved technologies by farmers.…”
Section: Table 3: Factors Influencing Multiple Climate Change Adaptation Practicescontrasting
confidence: 72%
“…Hence, they had sufficient skills in performing citrus cultivation. The farming experience may also put an influence on the technology adoption, as indicated in the study by Wongnaa et al (2018) that experience in farming is also a factor that affects the adoption of technology. The same result was shown by Wahyudi and Hasibuan (2011).…”
Section: Demographic Profile Of the Respondentsmentioning
confidence: 98%
“…The level of education generally affects the literacy, knowledge and the understanding of farmers. Several study results showed that technology adoption is influenced by educational level (Abebe et al, 2013;Khonje et al, 2015;Wongnaa et al, 2018).…”
Section: Demographic Profile Of the Respondentsmentioning
confidence: 99%
“…Industry experts believe the type of maize seeds used during cultivation presents a major opportunity to enhance farm output and profitability. Despite the high investment in extension education to encourage the adoption of modern improved seed technologies due to their high yield potential (Wongnaa et al , 2018); most maize farmers in Ghana continue to use their own saved maize seeds (i.e. Farmer Saved Maize Seed (FSMS)) [6] during production.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore assess the impact of the adopted seed technology using farm outcome variables which take into account both the cost and revenue aspect of each technology adopted. Per hectare output and revenue indicators have often been used as the main incentive to persuade farmers to adopt certified hybrid seed technologies (Wongnaa et al , 2018). However, the cost implication for adopting such improved varieties are often hidden and not so obvious to farmers until after adoption which could lead to disadoption.…”
Section: Introductionmentioning
confidence: 99%